A Systematic Literature Review on Competitive Advantage, Market-Based Resources, and The Development Of A General Theory Of Marketing - Fachri Afif; Abror; Vidyarini Dwita; Yunia Wardi (Journal of Indonesian Management, 2026)
Resource-Advantage (R-A) Theory has emerged as one of the most influential theoretical frameworks in marketing and strategic management for explaining how firms achieve and sustain competitive advantage through heterogeneous resources. Despite its growing application across various domains, including marketing strategy, innovation, customer relationship management, digital transformation, and sustainability, the literature remains fragmented. This study conducts a Systematic Literature Review (SLR) to synthesize the development, theoretical contributions, and future research directions of Resource-Advantage Theory in marketing. Following the PRISMA 2020 guidelines, articles published between 1995 and 2025 were identified from major academic databases, screened according to predefined inclusion and exclusion criteria, and analyzed using thematic synthesis. The findings reveal five dominant research themes: (1) competitive advantage and firm performance, (2) market-based resources and customer information assets, (3) marketing strategy and market segmentation, (4) digital transformation and analytical capabilities, and (5) sustainability and social impact. The review demonstrates that R-A Theory serves as a powerful integrative framework capable of bridging the divide between micro and macro marketing perspectives while providing a foundation for a general theory of marketing. The study concludes by proposing future research opportunities related to artificial intelligence, social commerce, customer engagement, and sustainable marketing.